NEW SPECIES OF STRONGYLID NEMATODE, LABIOSTRONGYLUS BIAKENSIS (NEMATODA: STRONGYLOIDEA) FROM MACROPUS AGILIS (GOULD, 1842) FROM BIAK, PAPUA - Endang Purwaningsih (BRIN Publishing (Penerbit BRIN), 2010)
Labiostrongylus biakensis, new species (Nematoda: Strongyloidea: Chabertiidae)was collected from the stomach of Macropus agilis (Agile Wallaby) in Papua-Indonesia. This species distinguished from its congeners by a combination of charactersincluding the shape of buccal capsule, and the female tail, the form of genital coneand spicule, and the proportion of the ovejector. A key to the species of Labiostrongylusis given.